Uso de materiales didácticos en la enseñanza remota y la psicomotricidad en los niños de cinco años en la Institución Educativa Inicial Nº 522 Isabel Sandoval Rodríguez, Caballococha 2022 - Torres Curitima, Gissela (2023)
The objective of the study was to determine the relationship between the use of teaching materials in remote teaching and psychomotor skills in five-year-old children at the Initial Educational Institution Nº 522 Isabel Sandoval Rodríguez, Caballococha 2022. The research was relational, correlational, transversal, non-experimental and was carried out in 108 children of the Initial Educational Institution No. 522. This research used purposive sampling, which means that the entire population was chosen. The observation technique and observation guide instruments were used for data collection. Additionally, the instrument was validated through the opinion of experts. The value of the Pearson correlation coefficient was obtained where r=0.040, so the correlation is Low, therefore, the hypothesis is rejected: There is no direct relationship between the use of teaching materials in remote teaching and psychomotor skills in five-year-old children at the Initial Educational Institution Nº 522 Isabel Sandoval Rodríguez, Caballococha 2022.